2016
DOI: 10.1180/minmag.2016.080.093
|View full text |Cite
|
Sign up to set email alerts
|

A review of the structural architecture of tellurium oxycompounds

Abstract: Relative to its extremely low abundance in the Earth's crust, tellurium is the most mineralogically diverse chemical element, with over 160 mineral species known that contain essential Te, many of them with unique crystal structures. We review the crystal structures of 703 tellurium oxysalts for which good refinements exist, including 55 that are known to occur as minerals. The dataset is restricted to compounds where oxygen is the only ligand that is strongly bound to Te, but most of the Periodic 4+ cations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 512 publications
3
130
0
Order By: Relevance
“…This type represents the most frequently observed coordination polyhedron of oxotellurates(IV) for which four-and five-coordinated Te IV atoms are also known [30,31]. The three Te-O bonds have lengths between 1.85 and 1.92 Å and three O-Te-O bond angles between 90° and 102°.…”
Section: Crystal Structures Of the Pbteo3 Polymorphs-general Featuresmentioning
confidence: 98%
“…This type represents the most frequently observed coordination polyhedron of oxotellurates(IV) for which four-and five-coordinated Te IV atoms are also known [30,31]. The three Te-O bonds have lengths between 1.85 and 1.92 Å and three O-Te-O bond angles between 90° and 102°.…”
Section: Crystal Structures Of the Pbteo3 Polymorphs-general Featuresmentioning
confidence: 98%
“…Each TeO 4 polyhedron is linked to four symmetry-related TeO 4 polyhedra by sharing corners, which leads to the formation of a three-dimensional framework structure. Characteristic for the crystal chemistry of tellurium(IV) oxides or oxotellurates(IV) (Christy et al, 2016), the 5s 2 electron lone pair situated at the Te IV atom is stereochemically active and points towards the open space of this arrangement (Fig. 1).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Grundler et al, 2013). Further study is clearly justified, given that Te forms the largest number of mineral species of any element relative to its crustal abundance (Christy, 2015), shows an enormous diversity of crystal structural architecture in its minerals and synthetic compounds, whole groups of which are of interest for their photonic and fast-ion conduction properties (Christy et al, 2016), and is frequently an indicator of economic gold deposits in the crust (Cook et al, 2009).…”
Section: +mentioning
confidence: 99%
“…While undertaking the review, we discovered that many Te compounds have reoccurring structural motifs (Christy et al, 2016) such as the Cu 2 Te ribbon found in frankhawthorneite , timroseite (Kampf et al, 2010e), paratimroseite (Kampf et al, 2010e) and bairdite (Kampf et al, 2013c), which suggested that Te oxysalt mineral structures form a structural hierarchy that might also correlate with paragenetic order, as do those noted above for other chemical classes of mineral. Testing this idea required a locality containing a large suite of Te minerals, and sufficient contact relationships between coexisting minerals for a paragenetic sequence to be deduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation